Guide-based interventions aimed at reducing physical restraints in intensive care unit: a systematic review and meta-analysis of randomized controlled trials - Ping, Yueli; Yang, Jianyan; Zheng, Yanming; Feng, Wanting; Huang, Zexi; Sha, Ruiqin; Cui, Nianqi; Tian, Ying (Frontiers in Medicine, 2025)
ObjectiveDespite widespread advocacy and organizational support for reducing the utilization of physical restraint (PR) in clinical settings, its application remains prevalent on a global scale. This study aims to identify and evaluate guide-based, high-quality interventions that can be effectively integrated into clinical practice to substantially reduce PR utilization rates.MethodsA comprehensive search of relevant databases was covered all available records from their establishment through November 10, 2024, including PubMed, the Cochrane library, Web of Science, CINAHL, EMBASE, the Joanna Briggs Institute (JBI), China National Knowledge Infrastructure (CNKI), Wanfang Data, China Science and Technology Journal Database (VIP), and Chinese BioMedical Literature Service System (SinoMed). The search specifically targeted randomized controlled trials (RCTs) that focused on guide-based interventions designed to reduce the utilization of PR in the intensive care unit (ICU). Two independent researchers systematically reviewed the literature, with each investigator independently extracting relevant data and assessing the methodological quality of included studies using standardized criteria. The subsequent meta-analysis was conducted using Review Manager software version 5.2.ResultsA total of 14 RCTs, involving 4,338 participants, were included in the analysis. The results indicated that guide-based interventions significantly reduced the PR rate (RR = 0.72, P < 0.001), PR time [weighted mean differences (WMD) = −248.5, P = 0.002], delirium incidence (RR = 0.53, P < 0.001), duration of delirium (WMD = −11.94, P = 0.008), unplanned extubation rate (RR = 0.36, P < 0.001), the other complications rate (RR = 0.36, P < 0.001), and duration of mechanical ventilation (WMD = −31.84, P = 0.005). Notably, in contrast to other outcomes, these interventions were associated with increased patient satisfaction (RR = 1.16, P < 0.001). However, there was no evidence to suggest that guide-based interventions reduced the length of ICU stay or patient agitated or anxiety rate (P > 0.05).ConclusionGuide-based interventions can effectively reduce the utilization of PR with patients in ICU. Employing a multidisciplinary team, adjusting patient assessment frequency by PR type and standardizing the PR assessment scale are possible to reduce the utilization of PR.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024623625, identifier: CRD42024623625.